1989
DOI: 10.1111/j.1651-2227.1989.tb11293.x
|View full text |Cite
|
Sign up to set email alerts
|

Septicaemia with Coagulase Negative Staphylococci in a Neonatal Intensive Care Unit Risk Factors for Infection, and Antimicrobial Susceptibility of the Bacterial Strains

Abstract: Eshali, H., Ringertz, S., Nyström, S. and Faxelius, G. (The Department of Paediatrics, Karolinska Hospital and St. Göran's Children's Hospital and the Department of Clinical Microbiology, Karolinska Hospital, Karolinska Institute, Stockholm, Sweden). Septicaemia with coagulase negative staphylococci in a neonatal intensive care unit. Risk factors for infection, and antimicrobial susceptibility of the bacterial strains. Acta Paediatr Scand Suppl 360: 127, 1989. Septicaemia caused by coagulase negative staphyloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 18 publications
3
1
0
Order By: Relevance
“…However, only 17 out of 31 episodes were classified as true catheter-related sepsis, defined as both positive blood culture and culture-positive intravascular catheter tip with CNS of identical resistance pattern. The role of CNS as major aetiologic agents of neonatal septicaemia, notably in VLBI, has been described in several reports during the past years (12)(13)(14)(15)(16)(17)(18)(19). The present results, by using stringent criteria for the definition of CNS sepsis, confirm former observations of these microorganisms as leading pathogens in the NICU environment, since increasing numbers of extremely low birthweight infants survive who seem to be particularly prone to severe infections caused by these ordinarily nonpathogenic skin commensals.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, only 17 out of 31 episodes were classified as true catheter-related sepsis, defined as both positive blood culture and culture-positive intravascular catheter tip with CNS of identical resistance pattern. The role of CNS as major aetiologic agents of neonatal septicaemia, notably in VLBI, has been described in several reports during the past years (12)(13)(14)(15)(16)(17)(18)(19). The present results, by using stringent criteria for the definition of CNS sepsis, confirm former observations of these microorganisms as leading pathogens in the NICU environment, since increasing numbers of extremely low birthweight infants survive who seem to be particularly prone to severe infections caused by these ordinarily nonpathogenic skin commensals.…”
Section: Discussionsupporting
confidence: 87%
“…CNS were the single most common aetiologic agent for neonatal septicaemia in this study, despite the fact that rather strict criteria for the evaluation of CNS-positive blood cultures were applied. In 28 of 31 episodes of CNS bacteraemia a central venous catheter was present by the time the blood culture was obtained, similar to the situation reported previously (12)(13)(14)(15)(16). However, only 17 out of 31 episodes were classified as true catheter-related sepsis, defined as both positive blood culture and culture-positive intravascular catheter tip with CNS of identical resistance pattern.…”
Section: Discussionsupporting
confidence: 72%
“…In 28 of 31 episodes of CNS bacteraemia a central venous catheter was present by the time the blood culture was obtained, similar to the situation reported previously (12)(13)(14)(15)(16). In 28 of 31 episodes of CNS bacteraemia a central venous catheter was present by the time the blood culture was obtained, similar to the situation reported previously (12)(13)(14)(15)(16).…”
Section: Discussionsupporting
confidence: 82%
“…Six patients had blood cultures that were positive for CNS, and five of these patients subsequently developed moderate or severe BPD (18). Previous studies have widely reported CNS in blood cultures from neonates and children, and these organisms are believed to be the leading cause of late-onset sepsis among low-birth-weight infants (4,8,11,12,15,23,24). Further research into the role of CNS in BPD is warranted, especially as methicillin-resistant CNS are becoming more prevalent within the community and in health care settings (1).…”
Section: Discussionmentioning
confidence: 99%